Scanning force microscope for in situ nanofocused X‐ray diffraction studies. (7th August 2014) - Ren, Zhe; Mastropietro, Francesca; Davydok, Anton; Langlais, Simon; Richard, Marie‐Ingrid; Furter, Jean‐Jacques; Thomas, Olivier; Dupraz, Maxime; Verdier, Marc; Beutier, Guillaume; Boesecke, Peter; Cornelius, Thomas W.
<x xml:space="preserve">Abstract</x> A compact scanning force microscope has been developed for in situ combination with nanofocused X‐ray diffraction techniques at third‐generation synchrotron beamlines. Its capabilities are demonstrated on Au nano‐islands grown on a sapphire substrate. The new in situ device allows for in situ imaging the sample topography and the crystallinity by recording simultaneously an atomic force microscope (AFM) image and a scanning X‐ray diffraction map of the same area. Moreover, a selected Au island can be mechanically deformed using the AFM tip while monitoring the deformation of the atomic lattice by nanofocused X‐ray diffraction. This in situ approach gives access to the mechanical behavior of nanomaterials.